Excuse giving, social decision making, and Bayesian statistics : the mathematical psychology of an attributional process - Franco, Víthor Rosa (2017)
Dissertação (mestrado)—Universidade de Brasília, Instituto de Psicologia, Programa de Pós-Graduação em Psicologia Social, do Trabalho e das Organizações, 2017.